Database and Expert Systems Applications 33rd International Conference, DEXA 2022, Vienna, Austria, August 22-24, 2022, Proceedings, Part I - Strauss, Christine; Cuzzocrea, Alfredo; Kotsis, Gabriele; Tjoa, A Min.; Khalil, Ismail (Cham : Springer International Publishing : Imprint: Springer, 2022)
This two-volume set, LNCS 13426 and 13427, constitutes the thoroughly refereed proceedings of the 33rd International Conference on Database and Expert Systems Applications, DEXA 2022, held in Vienna in August 2022. The 43 full papers presented together with 20 short papers in these volumes were carefully reviewed and selected from a total of 120 submissions. The papers are organized around the following topics: Big Data Management and Analytics, Consistency, Integrity, Quality of Data, Constraint Modelling and Processing, Database Federation and Integration, Interoperability, Multi-Databases, Data and Information Semantics, Data Integration, Metadata Management, and Interoperability, Data Structures and much more.
Knowledge Graphs -- Privacy-Preservation Approaches -- Deep Learning -- Smart Cities and Human Computing -- Advanced Machine Learning -- Warehousing Methodologies -- Time Series, Streams and Event Data -- Sequences and Graphs -- Neural Networks -- Efficient Data Processing Techniques -- Advanced Analytics Methodologies and Methods.
Keywords: Database management; Artificial intelligence; Application software; Software engineering; Information storage and retrieval systems; Data mining; Database Management System; Artificial Intelligence; Computer and Information Systems Applications; Software Engineering; Information Storage and Retrieval; Data Mining and Knowledge Discovery